PEMANFAATAN MESIN TETAS SEDERHANA UNTUK MENINGKATKAN PRODUKTIVITAS PENETASAN TELUR AYAM KAMPUNG PADA KELOMPOK TERNAK SUMBER TANI BARU DI KELURAHAN WUNDUBATU, KOTA KENDARI - Badaruddin, Rusli; Saili, Takdir; Prasanjaya, Putu Nara Kusuma; Kimestri, Asma Bio; Auza, Fuji Astuty; Sani, La Ode Arsad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
The free-range chicken farming group in Wundubatu Village faces problems of low productivity due to low natural egg hatch rates (40–50%) and dependence on parent stock. This community service program aims to introduce and apply appropriate technology in the form of a simple hatching machine to increase the hatchability of native chicken eggs. The implementation methods include coordination with partners, operational training on the hatching machine, technical assistance, and hatching trials. The results of the activity showed an increase in hatchability to 80-85%, an increase in the number of chicks produced, and an increase in farmers' knowledge and skills in artificial hatching management.